2011
DOI: 10.1186/1756-0500-4-100
|View full text |Cite
|
Sign up to set email alerts
|

Are mental health and binge drinking associated in Dutch adolescents? Cross-sectional public health study

Abstract: BackgroundDepression and anxiety disorders have a high disease burden and as many as 15% of young people report mental health problems. Binge drinking, which is a particularly harmful way of consuming alcohol, is common among secondary school students. The aim of this study was to examine the association between binge drinking and self-reported mental health in boys and girls aged 12 to 18 years.FindingsThis cross-sectional analysis was performed on data collected by the Community Health Service (GGD) Brabant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In this sense, binge drinking by individuals who are anxious and/or tend to become depressed could also be interpreted as a means of self-medication. Recent studies bear witness to higher levels of psychological morbidity among binge drinkers, who more frequently report typical symptoms of mental discomfort, stress and emotional problems, particularly anxiety, neurosis, depression (12,13). Hence the present study on the relationship between binge drinking in adolescence and psychopathological vulnerability, which aims at verifying, relationship between quantity of alcohol and psycho-behavioral problems: we expect that binge drinkers have more internalizing and externalizing disorders than nondrinkers or moderate drinkers.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, binge drinking by individuals who are anxious and/or tend to become depressed could also be interpreted as a means of self-medication. Recent studies bear witness to higher levels of psychological morbidity among binge drinkers, who more frequently report typical symptoms of mental discomfort, stress and emotional problems, particularly anxiety, neurosis, depression (12,13). Hence the present study on the relationship between binge drinking in adolescence and psychopathological vulnerability, which aims at verifying, relationship between quantity of alcohol and psycho-behavioral problems: we expect that binge drinkers have more internalizing and externalizing disorders than nondrinkers or moderate drinkers.…”
Section: Introductionmentioning
confidence: 99%
“…The sum score (range 5-30) was linearly transformed to vary from 0 to 100. A cut-off score of 60 was used to clasUnauthenticated Download Date | 12/16/16 1:18 PM sify moderate to poor mental health (e.g., Theunissen, Jansen, & van Gestel, 2011). A cut-off score of 60 produces the smallest error rate, as defined by yielding the highest sensitivity and specificity rates (Kelly, Dunstan, Lloyd, & Fone, 2008).…”
Section: Mental Healthmentioning
confidence: 99%
“…26 The relation between smoking and psychological distress is also consistent with what has been reported in literature. 11 Strandheim et al 30 observed an association in Norwegian adolescents between the number of alcohol intoxications and behavioral and attention problems, but the relation was not adjusted for other covariates. In our study, the relation between the 2 variables was stronger in younger adolescents, which suggests greater vulnerability in early adolescence when depressive symptoms increase rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…3 Various factors have been related to mental health problems in adolescence. 7 However, the role of physical exercise, 8,9 alcohol consumption, 10,11 and body weight remains uncertain. 7 However, the role of physical exercise, 8,9 alcohol consumption, 10,11 and body weight remains uncertain.…”
mentioning
confidence: 99%